Negative Affect and Counterproductive Workplace Behavior: The Moderating Role of Moral Disengagement and Gender - Samnani, Al-Karim; Salamon, Sabrina Deutsch; Singh, Parbudyal (2014)
There has been growing scholarly interest in understanding individual-level antecedents of counterproductive workplace behavior (CWB). While researchers have found a positive relationship between individuals’ negative affect and engagement in CWB, to date, our understanding of the factors which may affect this relationship is limited. In this study, we investigate the moderating roles of moral disengagement and gender in this relationship. Consistent with our hypotheses, we found that individuals with a greater tendency to experience negative emotions were more likely to engage in CWB when they had a higher propensity to morally disengage. Moreover, we found that this interacting relationship varied across men and women. We discuss the theoretical and practical implications of our findings and offer avenues for future research.
Keywords: Deviance; Gender; Moral Disengagement; Counterproductive workplace behaviors